Phytopharmacological Properties of Randia dumetorum as a Potential Medicinal Tree: An Overview - Patel Ritesh G, Pathak Nimish L, Rathod Jaimik D, Dr.L.D.Patel, Bhatt Nayna M (Journal of Applied Pharmaceutical Science)
Randia dumetorum family Rubiaceae is highly reputed ayurvedic medicinal tree commonly known as the Mainphal, Mindhal. A large deciduous thorny shrub grows up to 5 meters of height. It occurs in almost throughout India up to 4,000 ft attitude. It is found in Himalaya from jammu east words ascending to 1300 and from the Kashmir to east word’s up to 4000. It is seen in Gujarat, Tamilnadu forest of Dehradun, Suralik range, Bengal, Bihar, Orrisa & South Maharashtra and costal districts of south India. In dry deciduous forests in India. Root bark of Randia dumetorum contains triterpene, -1-keto-3-hydroxyoleanane, Bark of Randia dumetorum contains mannitol, saponins, coumarin glycosides, Leaves contain an iridoid-10- methylixoside. An iridoid glycoside, Ripe fruit contains glycosides, randioside A, mollisidial triterpenoid glycosides and randianin, six saponins-dumetoronins A to F. It cures abscess, ulcers, inflammation, wounds, tumours, skin diseases and have antibacterial activity. The pulp of fruit is believed by many practitioners to also have anthelmintic properties, and also used as an abortiffcient as folklore remedy. Various phytopharmacological evaluations have been reported in this literature for the important potential of the Randia dumetorum.
Keywords: Randia dumetorum, Phytopharmacological Properties, Medicinal plants.